Occupational health and safety in agriculture - a brief report on organization, legislation and support in selected European countries - Jakob, Martina Carola; Santa, Dushica; Holte, Kari Anne; Sikkeland, Inger Johanne; Hilt, Björn; Lundqvist, Peter (Institute of Rural Health, 2021)
Agriculture and forestry are among the most dangerous professions in Europe, with a high level of accidents affecting the sustainability and viability of the sector. International conventions, EU directives and national legislation build the fundamental basis for prevention. The aim of the study is to describe and categorize national mechanisms of occupational safety and health (OSH) for agricultural workers in Europe, to assess the extent of implementing safety regulation, the body in charge, and to give examples of health and safety initiatives.